Study on Productive and Morpholgical traits of Goat Kids in different Ecozones of Rolpa district - Azad, MH; Dahal, M; Ali, MS (Nepalese Veterinary Journal, 2023)
Goat is a domesticated small ruminant, reared by small farmers across the country primarily for meat production. Productivity of goat is often low, which could be related to several genetic and non-genetic factors. A field study was carried out to characterize, evaluate and estimate the effect of non-genetic factors on the hill goat kids during December, 2015 to August 2016 in different eco-zones of Rolpa district, mid-west Nepal. Altogether150 goat kids were selected for this study. Morphological attributes productive performances based on field monitoring and measurements within different altitudes of Rolpa were collected. Least square analysis was performed using Harvey (1990) computer software package, and means were compared using DMRT. The mean body weight of goat kids at birth, pre-weaning, weaning at 5 months’ age were 2.62, 6.34, 10.15 and 13.87 kg respectively. Birth weight of kids significantly differed with respect to altitude(P<0.01). Coat colour (P<0.05) of does and parity (P<0.001) of dams. Similarly, kidding rates of does significantly differed (P<0.05) with respect to colour and altitude. Body weight of the kid at weaning were significantly (P<0.05)correlated to body length, heart girth and wither height. Thus, the results of this study suggest that the performance of low altitude goat flocks was better than mid and high altitude goat flocks in Rolpa district in terms of production and reproduction traits. The selection of the best performing kids for higher weight gain could be done on the basis of both birth and weaning weights. This result could be attributed to superior genotype along with better management practices adopted by the farmers in Rolpa district.